Effects of substrate characteristics on the passivation performance of ALD-Al2O3 thin film for high-efficiency solar cells - 梁宗存 王殿磊 朱彥斌 (半导体学报：英文版, 2014)
Atom layer deposition （ALD）-Al2O3 thin films are considered effective passivation layers for p-type silicon surfaces. A lower surface recombination rate was obtained through optimizing the deposition parameters. The effects of some of the basic substrate characteristics including material type, bulk resistivity and surface morphology on the passivation performance of ALD-Al2O3 are evaluated in this paper. Surface recombination velocities of 7.8 cm/s and 6.5 cm/s were obtained for p-type and n-type wafers without emitters, respectively. Substrates with bulk resistivity ranging from 1.5 to 4 Ω · cm were all great for such passivation films, and a higher implied Voc of 660 mV on the 3 Ω · cm substrate was achieved. A minority carrier lifetime （MCL） of nearly 10 μs higher was obtained for cells with a polished back surface compared to those with a textured surface, which indicates the necessity of the polishing process for high-efficiency solar cells. For n-type semi-finished solar cells, a lower effective front surface recombination velocity of 31.8 cm/s was acquired, implying the great potential of （ALD）-Al2O3 thin films for high-efficiency n-type solar cells.